Endophyte-mediated biocontrol reduces the pathogenicity of Burkholderia glumae in rice seedlings (Oryza sativa L.) (2024)
ABSTRACT: Burkholderia glumae is the pathogen responsible for causing bacterial panicle blight, a disease that affects rice (Oryza sativa) and significantly impacts crop production and yield efficiency. Current control methods are mainly based on agrochemicals and are less effective against the emergence of new strains. It is, therefore, necessary to find alternative methods to reduce the impact of the pathogen in the field. This study aims to evaluate the possible biocontrol effect of endophytic bacteria isolated from rice against symptoms caused by the pathogen Burkholderia glumae in rice seedlings. Initial results from this research led to the identification of 16 endophytic isolates with characteristic in vitro PGPB. In the test on seedlings, the endophytic improved the vigor index values. Subsequently, three strains of B. glumae were assessed for their pathogenicity, involving the determination of severity levels and their impact on seedling physiology. Following this, the capacity of endophytic bacteria to ameliorate effects of the disease on rice seedling physiology was evaluated. The results of the study revealed that the endophytic isolates Ory09 and Ory59 exhibited the ability to reduce the severity of the disease, as well as inhibit the coleoptile and radicle impairment caused by B. glumae. The data indicated that these two isolates did not affect the vigor index concerning healthy controls.